Humulus lupulus beta-acid and 5-FU loaded nanoparticles as well as preparation method and application thereof

By loading hop β-acid and 5-FU into cross-linked sodium alginate and chitosan nanocarriers, a nanoparticle that can slowly release drugs in the colorectum is developed, solving the problem of drug difficulty in the existing technology. Targeting colorectal problems achieves better therapeutic effects and safety.

CN119326821APending Publication Date: 2025-01-21NINGXIA MEDICAL UNIVERSITY GENERAL HOSPITAL
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411456367.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively target the colorectal site to release drugs, resulting in poor results in the treatment of colorectal cancer and the side effects of the drugs are unavoidable.

Method used

Develop a nanoparticle loaded with hop β-acid and 5-FU, and achieve slow release of the drug by loading these active ingredients into a nanocarrier formed by cross-linking sodium alginate and chitosan.

Benefits of technology

The oral administration of 5-FU has been achieved, and the limitations of intravenous injection have been overcome. Nano particles have obvious pH response characteristics, which can slowly release drugs in the colorectal part, significantly improve the therapeutic effect of colorectal cancer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119326821A_ABST
    Figure CN119326821A_ABST
Patent Text Reader

Abstract

The invention provides humulus lupulus beta-acid and 5-FU loaded nanoparticles as well as a preparation method and application thereof, and belongs to the technical field of biological medicines. According to the preparation method disclosed by the invention, positive charge amino groups of chitosan and negative ions of a sodium alginate solution are quickly crosslinked to form a stable polymer by virtue of strong electrostatic interaction between the positive charge amino groups of the chitosan and the negative ions of the sodium alginate solution, and hops beta-acid and 5-FU are loaded in the polymer; the nano-particle delivery system loaded with humulus lupulus beta-acid and 5-FU, which carries a plurality of therapeutic drugs, is obtained. The nanoparticles loaded with hop beta-acid and 5-FU prepared by the invention can realize oral administration of 5-FU, and overcome the problem that the current 5-FU can only be administered by intravenous injection and cannot take effect by oral administration. Moreover, the nanoparticles are stable in performance, have an obvious pH response characteristic, are reduced in release under an acidic condition, can slowly release active ingredients, and have a good colorectal cancer treatment effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomedicine technology, and in particular to nanoparticles loaded with hop beta-acid and 5-FU, and a preparation method and application thereof. Background Art

[0002] Colorectal cancer (CRC) is a common gastrointestinal malignancy with a mortality rate of about 10%. At present, the clinical treatment effect of colorectal cancer is poor. The reason may be that the drug has been digested and absorbed when it reaches the stomach and small intestine, making it impossible for the drug to reach an effective therapeutic concentration in the lesion area. In order to treat this disease, patients have to increase the dosage of the drug, but the side effects of the drug are unavoidable, which seriously affects the normal life of patients.

[0003] Therefore, the preparation of carriers that can release drugs in a targeted manner in the colorectal area has obvious application value. In addition to the preparation of targeted drug delivery systems, the type and amount of drug delivery also affect the treatment of diseases. It has been reported that combined drug use not only improves the efficiency of treatment, but also reduces toxic side effects. Therefore, the development of dual-drug drug delivery systems to improve the therapeutic effect is imminent, and the co-administration of different types of drugs (hydrophilic and hydrophobic) is becoming a research hotspot and hot topic. In the study of drug delivery systems, it was found that most drugs are almost attached to the surface of the carrier, rather than evenly distributed in the carrier matrix. The researchers analyzed that the reason for the separation of drugs from particles may be caused by the lack of power required for the drug to migrate into the interior of the particles during the preparation process. In addition, most of the drugs attached to the surface of the carrier will be desorbed during the preparation and cleaning process. Therefore, loading drugs into the carrier can increase the drug loading capacity of the nanocarrier, reduce the cytotoxicity of the drug, and improve the therapeutic effect.

[0004] Polysaccharide-based nanomaterials are widely available, have good biocompatibility, and are widely used in the field of drug delivery. Chitosan (CS) is a polysaccharide with an annual output second only to cellulose in nature, and can be obtained by deacetylation of chitin. In terms of physical and chemical properties, CS is known for its degradability, non-toxicity, and non-immunogenicity. In addition, CS can be dissolved in acidic solutions to expand its range of applications. As a medicinal material, CS can be cross-linked with other polysaccharide materials to form a more complex system. Among the commonly used polysaccharides, sodium alginate (SAG) protects acid-sensitive drugs in gastric juice and enables drug delivery in the gastrointestinal tract. However, studies have found that when SAG is used as a drug delivery substrate, its drug encapsulation efficiency is low. In order to improve its shortcomings, the researchers chose to use calcium ions (Ca 2+) SAG and CS were cross-linked to form drug carriers to deliver peptides, insulin, nifedipine, methotrexate, lysine, cinnamaldehyde, etc., and in subsequent characterization studies, it was found that different active ingredients were successfully released from the new drug carriers and showed good biological activity. The ability of drug carriers to produce controlled drug release when delivering hydrophilic and hydrophobic drugs is the key to preparing dual-carrier drug delivery systems. Combination therapy of multiple drugs is currently a common method to improve the efficacy of various diseases, so it is beneficial to develop a delivery system that can carry multiple therapeutic drugs.

[0005] Due to the complexity of the causes of cancer, it is usually necessary to combine different types of treatments and multiple drugs. 5-FU has been widely recognized by society for the treatment of colorectal cancer, but in clinical applications, 5-FU is mostly administered intravenously. Although there are oral capecitabine drugs for the treatment of colorectal cancer, their side effects are obvious, so the development of 5-FU that can be administered orally is of great significance. In addition, modern pharmacological studies have reported that many plant active extracts have good anti-cancer effects, such as curcumin, paclitaxel and resveratrol. Interestingly, hops is a perennial, dioecious plant that has long been used in food and medical fields. In plant fraction analysis, researchers reported a large number of active ingredients found in hops. One of the active ingredients, β-acid, is extracted from the soft resin of hops and is an effective ingredient with antibacterial, anticancer and antioxidant effects. Previous research results have found that β-acid loaded in polysaccharide materials still maintains good biological activity, so it is necessary to further explore its application range.

[0006] The Chinese patent application number 202410680872.0, "An active targeting and responsive dual-drug synergistic nano-drug loaded micelle and its application", prepared an active targeting and responsive dual-drug synergistic nano-drug loaded micelle, but in the preparation process, improper handling of the organic reagents used will cause pollution and damage to the environment; Patent 2024106808720, an active targeting and responsive dual-drug synergistic nano-drug loaded micelle and its application, does not have pH dependence, so after entering the body, the astragalus polysaccharide it carries may be released at will, and it cannot effectively treat colorectal cancer.

[0007] Therefore, developing a drug that can be slowly released in the colorectal area is crucial for the treatment of colorectal cancer. Summary of the invention

[0008] The purpose of the present invention is to provide a nanoparticle loaded with hops β-acid and 5-FU and a preparation method and application thereof, and to develop a hops β-acid and 5-FU dual-drug delivery system with better colon cancer treatment effect.

[0009] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0010] The invention provides a nanoparticle loaded with hop beta-acid and 5-FU. The nanoparticle loaded with hop beta-acid and 5-FU is obtained by loading hop beta-acid and 5-FU in a nanocarrier formed by cross-linking sodium alginate and chitosan.

[0011] The present invention also provides a method for preparing nanoparticles loaded with hops β-acid and 5-FU, comprising the following steps:

[0012] The 5-FU solution and the β-acid solution were dissolved in the chitosan solution, stirred for the first time, and then the sodium alginate solution was added. After the second stirring, the calcium chloride solution was added, and the reaction, centrifugation, washing, and drying were performed to obtain nanoparticles loaded with hop β-acid and 5-FU.

[0013] Preferably, the mass ratio of 5-FU:β-acid:chitosan:sodium alginate is: 315-675:315-1035:250-350:250-350:90-110.

[0014] Preferably, the first stirring time is 20-60 min; the second stirring time is 1-20 min; and the reaction time is 0.5-1.5 h.

[0015] The present invention also provides an application of nanoparticles loaded with hops beta-acid and 5-FU in preparing a drug for treating colon cancer.

[0016] The beneficial effects of the present invention compared with the prior art are:

[0017] (1) The present invention utilizes the strong electrostatic interaction between the positively charged amino groups of chitosan and the negative ions of the sodium alginate solution to rapidly crosslink the two to form a stable polymer, and loads hop β-acid and 5-FU in the polymer, thereby obtaining a nanoparticle delivery system loaded with hop β-acid and 5-FU and carrying a variety of therapeutic drugs. In addition, the present invention mainly uses anhydrous ethanol when preparing nanoparticles loaded with hop β-acid and 5-FU, which will not cause damage to the environment and is safe and pollution-free.

[0018] (2) The nanoparticles loaded with hop β-acid and 5-FU prepared by the present invention can realize the oral administration of 5-FU, overcoming the problem that 5-FU can only be administered by intravenous injection and cannot be taken orally. In addition, the nanoparticles have stable performance, obvious pH response characteristics, reduced release under acidic conditions, and can stay in gastric juice for 2 hours, in small intestinal juice for 6 hours, and in the colorectum for 16 hours. It can slowly release active ingredients and has a good therapeutic effect on colorectal cancer. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0020] Figure 1 FTIR of different materials in Experimental Example 1 of the present invention, wherein (a) is CS; (b) is SAG; (c) is 5-FU; (d) is β-acids; (e) is CS / SAG; (f) is CS / SAG / 22.5β-acids+5-FU;

[0021] Figure 2 XRD of 5-FU, β-acids, SAG, CS, CS / SAG, CS / SAG / 22.5β-acids+5-FU in Experimental Example 1 of the present invention;

[0022] Figure 3 SEMs of different materials in Experimental Example 1 of the present invention, wherein (a1) is CS / SAG; (b1) is CS / SAG / 7.5β-acids+5-FU; (c1) is CS / SAG / 15β-acids+5-FU; (d1) is CS / SAG / 22.5β-acids+5-FU; Scalebars=10.0μm;

[0023] Figure 4 TEM of different materials in Experimental Example 1 of the present invention, wherein (a1) is CS / SAG; (b1) is CS / SAG / 7.5β-acids+5-FU; (c1) is CS / SAG / 15β-acids+5-FU; (d1) is CS / SAG / 22.5β-acids+5-FU; Scalebars=500nm;

[0024] Figure 5The physical properties, drug loading and encapsulation efficiency of the nanoparticles (CS / SAG / 7.5β-acids+5-FU, CS / SAG / 15β-acids+5-FU, CS / SAG / 22.5β-acids+5-FU) in Experimental Example 1 of the present invention;

[0025] Figure 6 It is the in vitro release spectrum of the nanoparticles in the absence of digestive enzymes in Test Example 1 of the present invention, wherein A is the in vitro release spectrum of β-acid in CS / SAG / 7.5β-acid+5-FU, B is the in vitro release spectrum of β-acid in CS / SAG / 15β-acid+5-FU, C is the in vitro release spectrum of β-acid in CS / SAG / 22.5β-acid+5-FU; D is the in vitro release spectrum of 5-FU in CS / SAG / 7.5β-acid+5-FU, E is the in vitro release spectrum of 5-FU in CS / SAG / 15β-acid+5-FU, and F is the in vitro release spectrum of 5-FU in CS / SAG / 22.5β-acid+5-FU;

[0026] Figure 7 is the in vitro enzyme release spectrum of the nanoparticles in Test Example 1 of the present invention, wherein A is the in vitro enzyme release spectrum of β-acid in CS / SAG / 7.5β-acid+5-FU, B is the in vitro enzyme release spectrum of β-acid in CS / SAG / 15β-acid+5-FU, C is the in vitro enzyme release spectrum of β-acid in CS / SAG / 22.5β-acid+5-FU; D is the in vitro enzyme release spectrum of 5-FU in CS / SAG / 7.5β-acid+5-FU, E is the in vitro enzyme release spectrum of 5-FU in CS / SAG / 15β-acid+5-FU, and F is the in vitro enzyme release spectrum of 5-FU in CS / SAG / 22.5β-acid+5-FU;

[0027] Figure 8 The cell viabilities of HCT116 (A and B), HT29 (C and D) and NCM460 (E and F) of Experimental Example 2 of the present invention;

[0028] Fig. 9 5-FU and Molecular docking of different nearby proteins;

[0029] Fig.10 It is β-acid (n-lupone) and Molecular docking of different proteins;

[0030] Fig.11 It is β-acid (colupone) and Molecular docking of different proteins;

[0031] Fig.12 It is a β-acid (adlupone) and Molecular docking of different proteins. DETAILED DESCRIPTION

[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0033] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0037] The present invention provides a method for preparing nanoparticles loaded with hops β-acid and 5-FU, the steps comprising:

[0038] Dissolve 5-FU and β-acid solution in chitosan solution, stir for 20-60 minutes for the first time, continue to add sodium alginate solution, stir for 1-20 minutes for the second time, add calcium chloride solution, react for 0.5-1.5 hours, centrifuge, wash and dry to obtain nanoparticles loaded with hop β-acid and 5-FU.

[0039] The mass ratio of 5-FU: β-acid: chitosan: sodium alginate is: 315-675: 315-1035: 250-350: 250-350: 90-110.

[0040] Example 1

[0041] Example 1 of the present invention provides a method for preparing nanoparticles loaded with hops β-acid and 5-FU, and the specific steps are as follows:

[0042] Preparation of CS solution: 300 mg of CS was accurately weighed and dissolved in 100 mL (2% v / v) acetic acid solution and stirred for 30 min to completely dissolve it to obtain a CS solution (3 mg / mL).

[0043] Preparation of SAG solution: Weigh 300 mg of SAG, dissolve it in 100 mL of H2O and stir for 30 min to obtain a SAG solution (3 mg / mL).

[0044] Preparation of CaCl2 solution: 100 mg CaCl2 was dissolved in 100 ml water to obtain CaCl2 solution (1 mg / mL).

[0045] Preparation of 5-FU solution: Dissolve 5-FU in distilled water to prepare a 5-FU solution with a concentration of 45 mg / mL.

[0046] β-acid / ethanol solution: β-acid was dissolved in ethanol to obtain a β-acid / ethanol solution with a concentration of 45 mg / mL.

[0047] Take 100mL CS solution, add 7.5mL 5-FU (45mg / mL) and 7.5mL β-acid / ethanol solution (45mg / mL), stir and react for 30min to obtain a mixed solution. Add 100mL SAG solution to the above solution and stir for 10min. Finally, add 50mL CaCl2 solution, react for 1h, centrifuge at 10000rpm (4℃) for 10min, and wash with distilled water 3 times. The dual drug-loaded nanoparticles CS / SAG7.5β-acid + 5-FU were prepared by freeze drying.

[0048] Example 2

[0049] Example 2 of the present invention provides a method for preparing nanoparticles loaded with hops β-acid and 5-FU, and the specific steps are as follows:

[0050] Preparation of CS solution: 300 mg of CS was accurately weighed and dissolved in 100 mL (2% v / v) acetic acid solution and stirred for 30 min to completely dissolve it to obtain a solution (3 mg / mL).

[0051] Preparation of SAG solution: Weigh 300 mg of SAG, dissolve it in 100 mL of H2O and stir for 30 min to obtain a final solution (3 mg / mL).

[0052] Preparation of CaCl2 solution: 100 mg CaCl2 was dissolved in 100 ml water to obtain a solution (1 mg / mL).

[0053] Preparation of 5-FU solution: Dissolve 5-FU in distilled water to prepare a 5-FU solution with a concentration of 45 mg / mL.

[0054] β-acid / ethanol solution: β-acid was dissolved in ethanol to obtain a β-acid / ethanol solution with a concentration of 45 mg / mL.

[0055] Take 100mL CS solution, add 15mL 5-FU solution and 15mL β-acid / ethanol solution, stir and react for 30min to obtain a mixed solution. Add 100mL SAG solution to the above solution and stir for 10min. Finally, add 50mL CaCl2, react for 1h, centrifuge at 10000rpm (4℃) for 10min, and wash with distilled water 3 times. The dual drug-loaded nanoparticles CS / SAG / 15β-acid + 5-FU were prepared by freeze drying.

[0056] Example 3

[0057] Example 3 of the present invention provides a method for preparing nanoparticles loaded with hop β-acid and 5-FU. The difference from Example 1 is that in Example 3, the added amounts of 5-FU (45 mg / mL) and β-acid (45 mg / mL) are both 22.5 mL, and CS / SAG / 22.5 β-acid+5-FU are obtained.

[0058] Test Example 1

[0059] Test Example 1 of the present invention The nanoparticles loaded with hop β-acid and 5-FU prepared in Examples 1-3 were tested by electron microscope scanning, infrared spectroscopy, X-ray diffraction, particle size and potential, drug loading and encapsulation efficiency, release and anticancer performance. The specific methods are as follows:

[0060] (1) Infrared spectroscopy

[0061] The nanoparticle raw materials were characterized by infrared spectroscopy. The experimental results of one of the raw materials, CS, are as follows Figure 1 (a) is shown. At 3373cm -1 The characteristic peaks appearing at 2888cm represent the intramolecular and intermolecular hydrogen bonds formed by the hydroxyl groups in the CS structure. The absorption peaks here are strong and broad. -1 The characteristic peaks of CH show the asymmetric and symmetric stretching vibration absorption. The amide bond present in the CS structure is at 1604 cm-1 and 1387cm -1 There are characteristic peaks near 1091cm, which are related to the vibration modes of NH (amide I, amide II and amide III) bonds. -1 Nearby is the CO stretching vibration in the chitosan structure.

[0062] The characteristic absorption peaks of SAG, another raw material constituting the delivery system, in the FTIR spectrum are as follows: Figure 1 (b) 3262cm -1 Belongs to the stretching vibration of -OH, 1604cm -1 The characteristic peak at 1024cm belongs to the asymmetric stretching vibration of C=O. -1 The characteristic peak at 1406cm represents the stretching of the glycosidic bond by CO. -1 The peak at represents the symmetric stretching vibration of carboxylic acid.

[0063] The characteristic FTIR absorption peaks of 5-FU are as follows Figure 1 (c) shows that at 3147, 1659, 1434 and 820 cm -1 A strong characteristic peak was detected at 1252 cm-1, which is due to the vibration of the imine stretching (amide II and amide III) and the aromatic ring in the 5-FU structure. Among them, the CF stretching vibration in the 5-FU structure may be at 1252 cm-1. -1 The characteristic peak of β-acid, another active ingredient, appears at 3195 cm -1 、2929cm -1 and 1659cm -1 , representing the vibration of -OH, CH and C=O bonds respectively.

[0064] When Ca 2+ When added as a cross-linking agent ( Figure 1 (e)), some vibrations of the chitosan amide bond cannot be observed, for example, in CS / SAG, 1661 cm -1 and 1604cm -1 The characteristic peaks of the 3+ In CS / SAG, the characteristic peaks of -COOH in SAG are at 1604 cm -1 and 1406cm -1 Move to 1587cm -1 and 1409cm -1 , indicating that -COOH and -NH 3+ and Ca 2+ In CS / SAG, OH is at 3500~3200cm -1The characteristic peak corresponding to the stretching vibration of CS / SAG becomes broader and stronger, indicating that the hydrogen bonding between the absorbed water molecules and CS / SAG is enhanced. Moreover, the delivery system is prepared under true acidic conditions. During the acidification process, the -COOH part is protonated. After CS / SAG is formed, the peak at 1714 cm -1 When the two drugs were added to CS / SAG at the same time, the FTIR spectrum changed again, and the characteristic peaks of β-acid and 5-FU also appeared. -1 The enhancement and broadening of the absorption peak at 1252 cm -1 The characteristic peak of 5-FU shifted to 1254 cm -1 In addition, compared with 1409cm -1 and 1023cm -1 Convert to 1428cm -1 and 1048cm -1 The shift changes of the above characteristic absorption peaks indicate that there are molecular interactions between CS / SAG and β-acid and 5-FU.

[0065] (2) XRD results

[0066] XRD technology is widely used to study the presence of drugs in polymer carriers, providing useful information for drug dissolution and mechanism studies. According to previous studies, some drugs are dispersed in particles in an amorphous or solid form, while others are loaded in a crystalline form after interaction, depending on the properties of the drug and the polymer. Figure 2 Shown

[0067] Figure 2 The diffraction results of 5-FU showed that strong diffraction peaks were observed at 2θ=16.7, 19.4, 24.3, 28.9, 31.7, 32.4, and 33.6°, indicating that 5-FU existed in a crystalline powder state. β-acid had obvious diffraction peaks at 2θ=8.6 and 28.9°, indicating that β-acid had crystallinity. The CS diffraction pattern had strong diffraction peaks at 2θ=11.9 and 20.2°, and the SAG diffraction pattern had strong diffraction peaks at 2θ=13.5 and 21.7°. However, the diffraction peak intensities of CS and SAG were not as sharp as those of 5-FU and β-acid, indicating that in these two polymers that form drug carriers, they mainly exist in crystalline form rather than in amorphous state. When CS and SAG were reacted with Ca 2+ When cross-linked, the formed polymer showed broad diffraction peaks in the diffraction pattern. When 5-FU and β-acid were added, β-acid (2θ=8.5°) and 5-FU (2θ=28.9°) diffraction peaks appeared in the diffraction pattern of the drug-loaded polymer, indicating that both drugs were present in the polymer in crystalline form.

[0068] Although obvious diffraction peaks were observed in all monomers that formed the polymer, only broad diffraction peaks were observed after the polymer was formed. It is possible that CS dissolved in acidic solution is positively charged and sodium alginate solution is negatively charged, which is due to the Ca 2+ When preparing the drug delivery system, 5-FU and β-acid are first added to the CS solution, and then the sodium alginate solution and CaCl2 solution are added. There are different ionic interactions during the reaction: there is a strong electrostatic interaction between the positively charged amino groups of CS and the negative ions of the SAG solution; there is an electrostatic interaction between the positively charged amino groups of chitosan and the two negatively charged drugs; and there is an electrostatic interaction between the negative ions of sodium alginate and CaCl2. 2+ Electrostatic interactions between the two. All these ionic interactions play an important role in the cross-linking and subsequent formation of drug-loaded nanoparticles. CS and SAG are biomacromolecules with a large amount of charge, so they cross-link quickly in solution to form stable polymers. However, 5-FU and β-acid are small molecules that cannot react quickly and immediately with macromolecules (CS and SAG), so both drugs exist in the polymer in a crystalline form after incorporation into the polymer.

[0069] (3) SEM, particle size and zeta potential analysis

[0070] Scanning electron microscopy is an effective method for observing the surface morphology and structure of materials. After freeze-drying, the prepared CS / SAG, CS / SAG / 7.5β-acid + 5-FU, CS / SAG / 15β-acid + 5-FU, CS / SAG / 22.5β-acid + 5-FU and other materials were observed. First, it was found that all four materials had a certain degree of aggregation, but the outline of the nanoparticles could still be clearly observed. Figure 3 As shown, the drug-loaded material has been successfully synthesized.

[0071] SEM and TEM results showed that Ca 2+ The drug carrier formed by cross-linked CS and SAG was sponge-like and the particles were aggregated. When 5-FU and β-acid were co-loaded with CS / SAG, the image showed more obvious particle size. Interestingly, the intermolecular interaction was enhanced with the increase of 5-FU and β-acid content.

[0072] The particle size (nm), PDI and zeta potential (mV) of the four materials are shown in Figure 4 Nanoparticles with different drug loadings were prepared and the effect of drug incorporation on the size characteristics of the material was investigated.

[0073] Figure 4It is shown that the ideal diameter of nanoparticles should be less than 200nm, which will prolong their residence time, cellular uptake and in vivo biodistribution. However, the benefits of extended circulation time and passive targeting strategies make smaller nanoparticles (~200nm, but>10nm) also suitable for delivering anticancer compounds to lesions. In the present invention, the particle size of the prepared nanoparticles was measured to be 198nm, 219nm, 297nm and 332nm using a particle size analyzer, and the particle size of the nanoparticles increases with the increase of 5-FU and β-acid content in the prepared nanoparticles.

[0074] After using transmission electron microscopy to analyze the morphology of the four nanoparticles, it was found that the strong interaction between the nanoparticles made it difficult to observe the particle size as in the SEM image, making it impossible to accurately measure the particle size with a transmission electron microscope. In addition, there was a difference between the particle size of the nanoparticles analyzed by the SEM image and the particle size data obtained by the particle size analyzer. It is reported that the reason for the difference between the two analysis results is the different environmental conditions to which the nanoparticles are exposed.

[0075] The polydispersity index (PDI) of the nanoparticles loaded with different contents of 5-FU and β-acid was 0.46, 0.58, 0.96, and 0.89, respectively. It has been reported that higher PDI values ​​are associated with lower uniformity. As the content of 5-FU and β-acid increases, their binding to the nanoparticles leads to a decrease in the polydispersity of the nanoparticles. Zeta potential is an important indicator to characterize the physical stability of nanoparticle suspensions and is generally considered to define properties related to the surface charge of nanoparticles. As the zeta potential increases, the stability of the drug is enhanced. On the other hand, if the value of the zeta potential decreases, the charged nanoparticle suspension cannot maintain a stable state. In the present study, the zeta potential value of each nanoparticle was in the range of -18.4 to -8.96 mV, indicating good system stability ( Figure 5 ). In the present invention, the zeta potential value of the particles prepared by the two-drug system is relatively high, and increases with the increase of 5-FU and β-acid content. The zeta potential characterizes the stability of the nanoparticles prepared by the composite drug.

[0076] Different initial concentrations of 5-FU and β-acid had significant effects on the EE and LC of drug-loaded nanoparticles. The encapsulation efficiency (EE) and drug loading rate (LC) of 5-FU and β-acid in nanoparticles were determined by UV spectrophotometry. The experimental results showed that the EE and LC of 5-FU and β-acid showed a trend of first decreasing and then increasing. When the addition amount of 5-FU and β-acid was 22.5mL, the EE of 5-FU and β-acid were 34.46% and 44.80%, and the LC were 11.82% and 11.23%, respectively. The reason why the EE and LC did not increase significantly in this study may be that the maximum loading of nanoparticles was reached at the initial administration of 5-FU and β-acid. When the addition ratio of 5-FU increased from 7.5mL to 22.5mL, the changes in EE and LC were 35.33% to 53.13% and 8.72% to 11.82%, respectively. The reason for the change in EE and LC may be that β-acid and 5-FU exist in the nanoparticles in a crystalline state. During the preparation of drug-loaded nanoparticles, the nanoparticles were washed several times with distilled water to remove the 5-FU on the outer surface of the nanoparticles. 5-FU and β-acid are on the outer surface of the nanoparticles. The study found that during the experiment and centrifugation process, the excess active ingredients on the surface of the nanoparticles would fall off.

[0077] (4) In vitro release and kinetic studies

[0078] The present invention uses dialysis to study the in vitro release characteristics of two drugs in nanoparticles. Figure 6 and Figure 7 It can be seen that the release of the drug experienced an initial burst release followed by a constant continuous release. Many studies have found that the initial burst release of the drug is due to the desorption and diffusion of the drug just attached to the surface of the nanoparticles. In subsequent release studies, the sustained and continuous release of the drug may be due to the continued expansion of the nanoparticles, resulting in the slow release of the drug encapsulated in the nanoparticles.

[0079] The release curves of β-acid and 5-FU from drug-loaded nanoparticles at 37°C and different pH (1.2, 6.8 and 7.8) are shown in Figure 2. Figure 6 (AC) and Figure 6 As shown in (DF). For drug-loaded nanoparticles with different β-acid contents, the maximum release of β-acid from CS / SAG / 7.5β-acid + 5-FU at pH = 1.2, 6.8 and 7.8 was 16.76%, 16.51% and 35.52%, respectively; the maximum release of β-acid from CS / SAG / 15β-acid + 5-FU was 28.89%, 49.60% and 52.74%, respectively; the maximum release of β-acid from CS / SAG / 22.5β-acid + 5-FU was 13.33%, 23.17% and 41.81%, respectively.

[0080] The above release results show that the release of β-acid in nanoparticles is sensitive to pH, and the total amount of drug released decreases with decreasing pH. Under acidic conditions, the lower total release of β-acid from drug-loaded nanoparticles may be related to the protonation of the polymer under acidic conditions. On the contrary, the release of β-acid in alkaline solution increased significantly, which may be because the alkaline conditions destroyed the original structure of the polymer and accelerated the release of β-acid. In addition, the present invention found that the release of β-acid in drug-loaded nanoparticles has significant pH dependence. The release of β-acid is reduced under acidic conditions, indicating that gastric juice can reduce the release of β-acid. Nanoparticles and positively charged nanoparticles are less likely to decompose under acidic conditions. On the contrary, the release of β-acid increases significantly under neutral conditions.

[0081] The study showed that the maximum release of CS / SAG / 7.5β-acid+5-FU at pH=1.2, 6.8 and 7.8 was 59.31%, 57.16% and 58.58% respectively; the maximum release of CS / SAG / 15β-acid+5-FU was 88.44%, 98.44% and 94.03% respectively; the maximum release of CS / SAG / 22.5β-acid+5-FU was 34.84%, 35.33% and 33.44% respectively. Figure 6 (EF). Combined with the changes in the data, it was reported that the 5-FU released from the nanoparticles did not seem to have pH-responsive properties. The total amount of drug released from the nanoparticles containing high concentrations of 5-FU showed a decreasing trend. The reason for this analysis may be that the concentration of 5-FU in the nanoparticles increased and there were interactions between the small molecules, which made it take more time for the drug to diffuse out of the nanoparticles. In addition, β-acid, as another drug, competed with the release of 5-FU.

[0082] After adding different types of digestive enzymes to the simulated fluid, the experimental results showed that the release of β-acid and 5-FU showed pH response characteristics ( Figure 7 (AC) and Figure 7 (DF)). It was found that the drug stayed in gastric fluid for 2 hours, in small intestinal fluid for 6 hours, and in colorectal fluid for 16 hours. The release characteristics of β-acid in simulated fluid containing digestive enzymes were similar to those in simulated fluid without digestive enzymes, and a small amount of drug was almost always released at pH = 1.2. The release of 5-FU from simulated fluid with added digestive enzymes appeared to have pH-responsive properties. Combining the release graphs with and without added enzymes, it was found that the addition of digestive enzymes had an effect on the release of the active ingredients in the nanoparticles.

[0083] Release kinetics was used to study the in vitro release behavior of nanoparticles and further explore their release mechanism. This study used the first-order, Higuchi, and Ritger-peppas release models for fitting and interpretation. The in vitro release pattern of drug-loaded nanoparticles is complex, so different models were used for fitting. The data fitting provided showed that the Higuchi release model had a lower R compared with the other two models. 2 To further explain the release mechanism of 5-FU and β-acid from nanoparticles, the Ritger-Peppas mathematical model was fitted using the obtained release data. 2 The results showed that the release model R2 of β-acids and 5-FU ranged from 0.6945 to 0.9887 (packages 1 and 2), and most of them were n<0.45, indicating that the release mechanism of the two drugs in nanoparticles was Fick's diffusion and the release mode was diffusion-controlled.

[0084] Table 1 Model fitting parameters of β-acid release curve

[0085]

[0086]

[0087] Table 2 Model fitting parameters of 5-FU release curve

[0088]

[0089]

[0090] Test Example 2

[0091] Test Example 2 of the present invention detected the cytotoxicity and molecular docking of the nanoparticles loaded with hop β-acid and 5-FU prepared in Examples 1-3, and the specific method is as follows:

[0092] HCT116, HT29 and NCM460 cells were selected to detect the toxicity of β-acid, blank nanoparticles (CS / SAG) and nanoparticles CS / SAG / 7.5β-acid + 5-FU (Example 1), CS / SAG / 15β-acid + 5-FU (Example 2) and CS / SAG / 22.5β-acid + 5-FU (Example 3). The cells were first allowed to grow freely in a 96-well plate for 6 h at a density of 1×10 4 The cells were attached to the wall of each well and the medium in the 96-well plate was replaced with the medium containing drug and incubated for 24 hours. The next day, the medium containing drug was replaced with fresh medium, 10 μL CCK-8 solution was added, and the cells were incubated at 37°C for 1 hour. The optical density (OD) of each well was measured at 450 nm using an ELISA reader. 5-Fluorouracil (5-FU) was used as a positive control. Figure 8The cytotoxicity was evaluated in a dose-dependent manner at the indicated concentrations, and the results are shown in Figure 8 shown.

[0093] Figure 8 The results showed that at a high concentration of 80 μg / mL, CS / SAG showed low cytotoxicity to both HCT116 and HT29 and had good biocompatibility. It is worth noting that with increasing concentrations, the drug-loaded nanoparticles had an inhibitory effect on the growth of colorectal cancer cells, which may be due to the cytotoxicity of β-acid and 5-FU when released under physiological pH (~7.4).

[0094] At the same time, the dual-loaded nanoparticles (80 μg / mL) showed concentration-dependent cytotoxicity to HCT116 and HT29, with cell viability of HCT116 and HT29 being 54% and 67%, respectively. In contrast, high concentrations of the positive drug 5-FU had cell viability of 55% and 76% for HCT116 and HT29, respectively. Compared with the inhibitory effect of pure β-acid on colorectal cancer cells, the viability of HCT116 and HT29 cells at high concentrations (80 μg / mL) was 25.9% and 57.2%, respectively. The reason for the difference in the inhibitory effect of pure β-acid and drug-loaded nanoparticles on cells may be that the mass of β-acid and nanoparticles in the experiment is the same, but the actual content of β-acid in the drug-loaded nanoparticles is lower than that of pure β-acid. Analysis of two different colorectal cancer cells showed that the cytotoxicity of drug-loaded nanoparticles was different, which can be attributed to the difference in the intracellular environment of the two cells.

[0095] The crystal structures of human cyclin-dependent kinase 2, CDK2 (PDB ID: 2A4L), matrix metalloproteinase-2 (PDB ID: 1HOV), poly ADP-ribose polymerase-1 (PDB ID: 1UK0), Chk1 (PDB ID: 2R0U), nitric oxide synthase (PDB ID: 3E7G), cytochrome P450 CYP17A1 (PDB ID: 3RUK), Cyclin A (PDB ID: 6GUE), TRAF2 (PDB ID: 2X7F) and apoptosis regulator Bcl-2 (PDB ID: 4LXD) were obtained from the protein database. The downloaded enzyme proteins were used to remove water molecules and ligands from the enzyme proteins for subsequent docking experiments using PyMOL software.

[0096] Considering that β-acid is mainly composed of three homologous molecules (n-lupulone, cullupone and adlupulone), this study studied them separately. 5-FU and β-acid were constructed as ligand molecules using ChemDraw software, and the ligand molecules were optimized using Gaussian method. Molecular docking was performed using Hex 8.0 version software, and the optimal docking result was selected. The docking results were visualized and analyzed using PyMOL1.7 software. The results are shown in the figure. Figure 9-12 As shown in Table 3.

[0097] Table 35 - Molecular docking of FU / β-acid interactions with proteins

[0098]

[0099]

[0100]

[0101]

[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A nanoparticle loaded with hops β-acid and 5-FU, characterized in that: The nanoparticles loaded with hop beta-acid and 5-FU are obtained by loading hop beta-acid and 5-FU in a nanocarrier formed by cross-linking sodium alginate and chitosan.

2. A method for preparing nanoparticles loaded with hop β-acid and 5-FU as claimed in claim 1, characterized in that: The steps include: The 5-FU solution and the β-acid solution were dissolved in the chitosan solution, stirred for the first time, and then the sodium alginate solution was added. After the second stirring, the calcium chloride solution was added, and the reaction, centrifugation, washing, and drying were performed to obtain nanoparticles loaded with hop β-acid and 5-FU.

3. The method for preparing nanoparticles loaded with hop β-acid and 5-FU according to claim 2, characterized in that: The mass ratio of 5-FU:β-acid:chitosan:sodium alginate is:315-675:315-1035:250-350:250-350:90-110.

4. The method for preparing nanoparticles loaded with hops β-acid and 5-FU according to claim 2, characterized in that: The first stirring time is 20-60 min; the second stirring time is 1-20 min; and the reaction time is 0.5-1.5 h.

5. Use of nanoparticles loaded with hops β-acid and 5-FU prepared by the preparation method of nanoparticles loaded with hops β-acid and 5-FU according to claim 1 or any one of claims 2 to 4 in preparing drugs for treating colon cancer.

Citation Information

Patent Citations

  • Active targeting and response type double-drug-loading synergistic nano drug-loading micelle and application thereof

    CN118634194A